Optimization of thin-wall structures using hybrid gravitational search and Nelder-Mead algorithm - Yıldız, Ali Rıza; Kurtulus, Enes; Demirci, Emre; Yıldız, Betül Sultan; Karagöz, Selçuk (Carl Hanser Verlag, 2016)
In literature, a lot of research works have been presented on crashworthiness in order to develop crash performance of vehicles and thin-wall structures. In this research, a new hybrid optimization algorithm based on gravitational search algorithm and Nelder-Mead algorithm is introduced to improve crash performance of vehicles during frontal impact. The results show that the hybrid approach is very effective to develop crash performance of the vehicle components and thin-wall structures.
Keywords: Thin-wall structures; crashworthiness; automotive; optimization algorithm